A new species of Lestrolepis from the Red Sea, with redescription of Lestrolepis pofi (Harry, 1953) (Aulopiformes: Parelepididae) - Ho, Hsuan-Ching; Golani, Daniel (Zootaxa, 2019)
A new species of the genus Lestrolepis is described based on 6 specimens collected from the Red Sea. The species differs from the congeners in having 31‒34 anal-fin rays, 63‒65 total lateral-line scales, 28‒30 prehaemal vertebrae and 79‒81 total vertebrae. Lestidium pofi Harry, previously recognized as a junior synonym of “Lestrolepis” luetkeni (Ege), is recognized as a valid species of Lestrolepis. A redescription of pofi is provided, based on specimens collected from off Hawaii, Japan, Madagascar and Australia.